Vitamin D status in 3-6-year-old children of Mananthavady ICDS block in Wayanad, Kerala, India - Khan, Arif Mohamed; Sindhu, T. G.; Vijayakumar, M. (International Journal of Contemporary Pediatrics, 2018)
Background: Despite plenty of sunlight, vitamin D deficiency has been reported in both urban and rural population in India. This study was conducted to estimate the prevalence of Vitamin D deficiency in children between 3-6 years of age group belonging to Mananthavady ICDS block of Wayanad and to identify the sociodemographic variables affecting its level. Methods: This descriptive cross-sectional study was conducted from December 2014 to June 2015. 140 children were selected from 20 Anganawadis in Mananthavady ICDS block in Wayanad district of Kerala state by random methods. After taking relevant history and conducting detailed clinical examinations, blood samples were taken to assess 25(OH) Vitamin D, calcium, phosphorous and alkaline phosphatase levels. Statistical analysis was done using PASW software. Calculations of means were done using descriptive statistics and comparative analysis was done using independent T test. Results: Out of the 140 children 51 belonged to tribal community. The mean 25(OH) Vitamin D level was 22.7ng/ml. 47.1% of the population had deficient, 35% insufficient and 17.9% adequate Vitamin D levels. There was no statistically significant difference in Vitamin D levels between children of tribal and non-tribal community. There was significant increase in Vitamin D levels during summer when compared to that of winter and autumn seasons. Conclusions: There is a high prevalence of vitamin D deficiency among the rural children of 3-6-year age of Mananthavadi ICDS block. The Vitamin D levels were almost equal between the tribal and non-tribal children. Vitamin D levels are significantly higher during summer when compared to other seasons.